Norwegian banks' net interest income and macroeconomic developments over the past 30 years - Ragna Alstadheim; Rønnaug Melle Johansen (Norges Bank, 2023)
Banks' profitability is their first line of defence against losses, and net interest income is banks' main source of revenue. Since the policy rate hikes began in 2021, net interest income has increased substantially relative to assets, strengthening banks' loss-absorbing capacity. We use a VAR model to analyse what has affected Norwegian banks' net interest income relative to assets over the past 30 years. Historically, a higher policy rate has typically pulled up net interest income, while heightened market uncertainty has pulled down net interest income. In addition to the policy rate, cost-efficiency improvements help explain the substantial reduction in net interest income relative to assets observed since the 1990s. The increase during 2022 is largely caused by policy rate hikes from a low level during the pandemic. The increase reflects in part the fact that banks have more interest-bearing assets than interest-bearing debt and other factors such as developments in banks' interest margins. Using the VAR model, we show that banks' net interest income is procyclical, which supports the use of time-varying capital requirements.
hdl:11250/3166366
Keywords: 330